Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 151 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Lithodes maja (Linnaeus, 1758)", "Country is United Kingdom of Great Britain and Northern Ireland" ] } The dataset includes 151 records from 15 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000043-150523225239109/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences